If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7h + -13 = 50 Reorder the terms: -13 + 7h = 50 Solving -13 + 7h = 50 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 7h = 50 + 13 Combine like terms: -13 + 13 = 0 0 + 7h = 50 + 13 7h = 50 + 13 Combine like terms: 50 + 13 = 63 7h = 63 Divide each side by '7'. h = 9 Simplifying h = 9
| Q=12+0.25q | | -2.5n+8.7=5.45 | | S-15=15.43 | | 40-(-39)= | | d-50.4=6.6d | | -x-13=3x+19 | | 3x=4-6t | | -x=-6+y | | -8(x+4)=2x+48 | | 8m-29=35 | | 28-2(5Y-4)=-4 | | x^2-14x-216=0 | | 7x+21=3x+9 | | 12[5-2(3-4)]=-36 | | 6y-13=47 | | -40a^2+11a+30=0 | | 6x-11=2x+25 | | 5+25(25-x)=5.65 | | 4a^2-61a+225= | | z=6#960;xy | | x^2-14x+216=0 | | 4(3z-2)=52 | | 2(x-15)=20 | | 5y=-7x+15 | | ln(3x)+ln(x)=ln(12) | | 50+-4x=2 | | f(x)=sqrt(4(9)-16) | | 4x+2x+2+2=36 | | 7a+95386b=5245 | | 4[5-(-9)(4)+2]=-156 | | 4x^8-61x^4+225= | | 1024(x)=x-252 |